Synthesis of Vanadium (III) Doped Anatase TiO2 by Solid State Reaction Method - Aini, Nur; Ningsih, Rachamawati (ALCHEMY, 2016)
Anatase of Titanium dioxide (TiO2)Â  was doped with vanadium ions (V3+), at doping levels ranging from 0.3, 0.5 to 0.7 atomic percentage in order to increase its photocatalytic activity under visible light irradiation. Vanadium doped TiO2 was synthesized by solid state reaction method. Its physicochemical properties characterized by powder X-ray diffraction (XRD) and UV-Vis diffuse reflectance spectroscopy (DRS). Doping with V(III) resulted in a single phase structure of anatase TiO2 with nanosize crystal ranging from 53.06 to 59.59 nm. Vanadium doping also resulted in a red-shift of the photophysical response of TiO2 that was reflected in an extended absorption in the visible light between 400 and 700 nm.